Pencegahan insiden keselamatan pasien menggunakan patient safety enhancement strategy berbasis milieu therapy - Saraswati, Kristanti Indah; Pratiwi, Arum; Hudiawati, Dian (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Patient safety is a crucial aspect of healthcare services that must be a top priority for hospitals. Patient safety incidents can lead to serious injuries, increased healthcare costs, and damage to institutional reputation. Therefore, effective strategies are needed to prevent such incidents, one of which is the implementation of Milieu Safety, which emphasizes creating a safe and supportive environment for patients. Purpose: To examine and evaluate efforts to prevent patient safety incidents using the patient safety enhancement strategy based on milieu therapy. Method: This study employed a quasi-experimental design with a pretest-posttest nonequivalent control group approach. The sample consisted of 220 hospitalized patients, divided into intervention and control groups. Data were collected through the Safety Satisfaction in Healthcare Questionnaire (SSHQ), patient safety incident reports, and observations of Milieu Safety implementation using the Patient Care Safety Assessment Tool (PCSAT). Data analysis was conducted using the Mann-Whitney test to compare differences between the two groups. Results: The intervention group that implemented the Milieu Safety strategy showed a significant increase in patient satisfaction (p = 0.005) and maintained stability in patient safety incidents compared to the control group. Conclusion: The Milieu Safety strategy is effective in preventing patient safety incidents and improving the quality-of-care satisfaction. Integration of this principle into nursing Standard Operating Procedures (SOPs) is highly recommended. Keywords: Milieu Therapy; Patient Safety Enhancement Strategy; Patient Safety Incident Prevention. Pendahuluan: Keselamatan pasien adalah aspek penting dalam pelayanan kesehatan yang harus menjadi prioritas utama rumah sakit. Insiden keselamatan pasien dapat menyebabkan cedera serius, meningkatkan biaya, dan merusak reputasi. Oleh karena itu, diperlukan strategi efektif untuk mencegahnya, salah satunya melalui penerapan milieu safety yang menekankan pada terciptanya lingkungan aman dan mendukung bagi pasien. Tujuan: Untuk menelaah dan menilai upaya pencegahan pencegahan insiden keselamatan pasien menggunakan patient safety enhancement strategy berbasis milieu therapy. Metode: Penelitian dengan desain quasi-experimental menggunakan pendekatan pretest-posttest nonequivalent control group design. Sampelnya terdiri dari 220 pasien rawat inap yang dibagi menjadi kelompok intervensi dan kontrol. Data dikumpulkan melalui kuesioner kepuasan pasien (SSHQ), laporan insiden keselamatan, dan observasi penerapan Milieu Safety menggunakan Patient Care Safety Assessment Tool (PCSAT). Analisis data dilakukan dengan uji Mann-Whitney untuk membandingkan perbedaan antara kedua kelompok. Hasil: Kelompok intervensi yang menerapkan strategi milieu safety menunjukkan peningkatan signifikan dalam kepuasan pasien dengan p-value 0.005 dan stabilitas insiden keselamatan pasien, dibandingkan kelompok kontrol. Simpulan: Strategi milieu safety efektif dalam mencegah insiden keselamatan pasien dan meningkatkan kepuasan layanan perawatan. Integrasi prinsip ini dalam Standar Prosedur Operasional (SPO) keperawatan sangat direkomendasikan. Kata Kunci: Milieu Therapy; Patient Safety Enhancement Strategy; Pencegahan Insiden Keselamatan Pasien.